Manipulating the consequences of tests: how Shanghai teens react to different consequences. Issue 5 (17th August 2020) - Zhao, Anran; Brown, Gavin T. L.; Meissel, Kane
ABSTRACT: Students' test-taking motivation has been found to be a predictor of performance. This study tests whether Shanghai students' conceptions of tests and test-taking motivation differ when the consequence of tests have different foci (i.e., none, country, or personal). A between-subjects experiment with vignette instructions systematically assigned 1, 003 Shanghai senior secondary school students to one of the three vignettes. Students' conceptions of tests and test-taking motivation scales were evaluated using factor analyses. Invariance testing suggested invariant relationships between the two constructs across the three groups. Students' general conception of tests meaningfully predicted their reported effort ( β = .18). Latent mean analyses suggested that students' reported effort, anxiety, and importance were not significantly different between country at stakes and personal stakes groups, but higher than when no consequences were attached. This study suggests that Shanghai students' test-taking attitudes may contribute to high effort and consequently high performance on international large-scale assessments.